(3EbJUGO GdShb h GdYhdeI GdHOjdI (B/s - (3GdehShj, VjGA eLjOs ((3GdLRGFQ(B: s (3OGQ gheg(B, s, 2009)
1)(3bhGYO GbJUGO GdShb GdHOjdI (B: (3JONd GdOhdI aj GdfTGW GdGbJUGOj , eHOC GdMQjI h JONd GdOhdI aj GdfTGW GdGbJUGOj , GdShb aj GdGSdGe h GdefGaSI ZjQ GdeTQhYI h GdeYGedGJ GdeefhYI aj GdShb , JMOjO GdGSYGQ h eQGbHI GdGShGb , GdGMJcGQ (B2) (3GdYhdeI GdHOjdI (B: (3GdCeI GdGSdGejI h YGdejI GdOYhI GdGSdGejI , GdMQH aj GdGSdGe h GdJWhQ GdacQj aj GdYGde GdGSdGej h MhGQ GdMVGQGJ , hdGOI GdGSdGe aj GdZQH GdeYGUQ h CNjQG GdGSdGe h YhdeI GddjHQGdjI(B.s
Keywords: (3EbJUGO GdShbs; (3GdGbJUGOs; (3GdYhdeIs